Development of Augmented Reality (AR)-Based Flash Card Media in Science Learning for Fifth Grade Elementary School Students - Deby Anjelina; Andri Valen; Cahyo Dwi Andita (EDUJAVARE: International Journal of Educational Research, 2026)
Learning in its concept is to teach students to acquire knowledge. In the learning of science at the elementary school level (SD) is directed at improving skills in analyzing and understanding interrelated social and natural concepts. This study aims to develop a valid, practical, and effective Flash Card media based on Augmented Reality in learning science class V SDN 3 Lubuklinggau. This type of research is Research and Development with the ADDIE development model. The subjects of this study were students of class V SDN 3 Lubuklinggau. Data collection techniques used observation, interviews, questionnaires, tests and documentation. Based on the results of the validity analysis of the Flash Card media based on Augmented Reality cultural heritage material in Indonesia using Aiken's V shows an assessment of the language validator of 0.88, the media validator of 0.94, and the material validator of 0.92 meeting the validity criteria. Analysis of the assessment of the teacher and student practicality sheets obtained that the Flash Card media based on Augmented Reality meets the criteria of very practical with an average score of 81.75%. Then the effectiveness assessment analysis obtained an average N-Gain score of 0.72 with a high category. Based on the results of the study, it can be concluded that the Augmented Reality-based Flash Card media is proven to be valid, practical, and effective so that it is suitable for use in the material of Chapter 7 Cultural Heritage in Indonesia for class V of SDN 3 Lubuklinggau.